Cardiac Resynchronization Therapy: A 4-Year Review of Our Experience - EDAFE, EMMANUEL AUCHI; Iseko, Iseko Iyoko; Dodiyi-Manuel, Sotonye Tamunobelema (International Journal of Innovative Research in Medical Science, 2022)
Introduction: Cardiac Resynchronization therapy (CRT) is very significant in the management of Heart Failure with significant electrical dyssynchrony. This dyssynchrony is measured using QRS duration on the ECG. CRT has been shown to reduce mortality and improve symptoms in heart failure. The objective of the study is to review 4-year experience in CRT implantation, complications and challenges of implantation. Methods and materials: This was a retrospective study. We searched cath labs of Bayelsa Specialist Hospital, Cardiocare Hospital and retrieve all the CRT implanted within 1st January, 2018 and 30th June, 2022. Data collected were indications, duration of implant, complications, failure of implant and reason for the failure. Results: A total of 32 CRT were implanted during the review period. There were 20 men who received the device. CRT-D implanted were twenty-eight, with four CRT-P implanted. The mean implant duration was 2 hours 40 minutes. Conclusion: CRT is now commonly implanted with very high success rate. The complication ranges from non to mild and there is dramatic patient improvement.